Stochastic dynamic macroeconomics : theory and empirical evidence - Gong, Gang, 1959-; Semmler, Willi (Oxford ; New York : Oxford University Press, 2006)
The book provides an interesting and readable discusion of alternative paradigms in macro economics, and illustrates the failure of the Dynamic General Equilibruim models when based on estimated parameters as compared to calibrated values.
Includes bibliographical references (p. 189-199) and index.
nmn 02/05/13
Loans
Keywords: Macroeconomics -- Mathematical models; Equilibrium (Economics) -- Mathematical models; Business cycles -- Mathematical models; Keynesian economics -- Mathematical models; Stochastic analysis